Measured and simulated thermoelectric properties of FeAs2−xSex (x = 0.30–1.0): from marcasite to arsenopyrite structure. Issue 5 (31st July 2020) - Perez, Christopher J.; Devlin, Kasey P.; Skaggs, Callista M.; Tan, Xiaoyan; Frank, Corey E.; Badger, Jackson R.; Kang, Chang-Jong; Emge, Thomas J.; Kauzlarich, Susan M.; Taufour, Valentin; Kotliar, Gabriel; Lapidus, Saul H.; et al.
Abstract : FeAs2− x Se x exhibits structural transition at x = 0.65, and a low lattice thermal conductivity (0.22 W m −1 K −1 ) at x = 0.5. Abstract : FeAs2− x Se x ( x = 0.30–1.0) samples were synthesized as phase pure powders by conventional solid-state techniques and as single crystals ( x = 0.50) from chemical vapor transport. The composition of the crystals was determined to be Fe1.025(3) As1.55(3) Se0.42(3), crystallizing in the marcasite structure type, Pnnm space group. FeAs2− x Se x (0 < x < 1) was found to undergo a marcasite-to-arsenopyrite ( P 21 / c space group) structural phase transition at x ∼ 0.65. The structures are similar, with the marcasite structure best described as a solid solution of As/Se, whereas the arsenopyrite has ordered anion sites. Magnetic susceptibility and thermoelectric property measurements from 300–2 K were performed on single crystals, FeAs1.50 Se0.50 . Paramagnetic behavior is observed from 300 to 17 K and a Seebeck coefficient of −33 μV K −1, an electrical resistivity of 4.07 mΩ cm, and a very low κ l of 0.22 W m −1 K −1 at 300 K are observed. In order to determine the impact of the structural transition on the high-temperature thermoelectric properties, polycrystalline FeAs2− x Se x ( x = 0.30, 0.75, 0.85, 1.0) samples were consolidated into dense pellets for measurements of thermoelectric properties. The x = 0.85 sample shows the best thermoelectric performance. The electronic structure of FeAsSe was calculated with DFT and transport properties were approximately modeled above 500 K.